Acute Brucellosis Presenting with Bleeding Tendency due to Isolated Severe Thrombocytopenia - M. Aon; T. Al-Enezi (Case Reports in Infectious Diseases)
Mild anemia and leukopenia are the most common hematologic findings in the course of acute brucellosis. Severe form of thrombocytopenia is less frequently reported. We describe a case of acute brucellosis in a 20-year-old man, who presented with fever, purpuric skin lesions, epistaxis, and hematuria. The absolute platelet count was 2 × 109/L. The patient was diagnosed as suffering from brucellosis on the basis of a strongly positive serologic reaction and was treated with antibiotics and a short course of corticosteroids, with a rapid rise in platelet count. Brucella infection can cause immune-mediated thrombocytopenia that is reversible after appropriate antimicrobial therapy and steroid treatment.